Mainan Edukasi untuk Kegiatan Edukasi Hemat Energi “Earth Hour Bandung” - Afif Muhammad Fadhil Utomo; Sulistyo Setiawan (Jurnal Desain Indonesia., 2022)
This research is the process of designing an educational toy product regarding environmentally friendly alternative energy for the SIMARGI (Education Saving Energy) community "Earth Hour Bandung" activity for elementary school. This research is motivated by the need for the "Earth Hour Bandung" community which has SIMARGI program activities, this activity is an activity to introduce and educate about the environment and energy to kindergarten children aged 4-5 years to college teenagers aged 21-23 years. In this design, elementary school becomes a case study of the problem because elementary schools are the largest contributors to participants. The author also found the problems experienced by the "Earth Hour Bandung" community so that the authors and parties from the community discussed to analyze the problems and find solutions. From the results of the discussion, the community has a problem, namely that it still needs the right learning media in order to help elementary school children better understand the material provided by the community, therefore the right product is needed to help run SIMARGI activities at elementary school. The design process was carried out through a design thinking process approach and thus resulted in the design of educational toys for the “Earth Hour Bandung” community when carrying out SIMARGI activities in elementary schools.